Development and evaluation of two-parallel crawler robot by using proportional controller - Mohamed Kassim, Anuar; Mohd Aras, Mohd Shahrieel; Shukor, Ahmad Zaki; Jaafar, Hazriq Izzuan; Ab Rashid, Mohd Zamzuri; Baharom, Mohamad Faizal; Jafar, Fairul Azni (Penerbit UTM Press, 2015)
Nowadays, the crawler type robots are widely used in rescuing and inspection missions. However, most of the existing crawler type robots available now are not moving consistently in one direction. This project aim on design and develop a crawler type robot which can pass through several types of terrain as well as to analyze and evaluate the performance of developed crawler type robot in term of its accuracy and repeatability by using Proportional (P) controller. Moreover, the terrains involved in this project are focused only on flat surface and rough surface respectively. The experiments are conducted in two methods which are lab test and field test. Lab test is conducted on flat surface while field test is conducted on rough surface. Then, the performance (accuracy and repeatability) of both experiments will be measured. As the results, the experiments which have been conducted on both methods by using Proportional (P) controller are implemented successfully.